Vibrio cholerae bacteremia (non-O1/non-O139): case report - Motta, Juan Camilo (2020)
Vibrio cholerae (non-O1/non-O139) is an uncommon pathogen that causes infection in humans, it is a free-living microorganism in river and sea waters, where it colonizes fish and shellfish, which are the main transmission sources. We present the case of a 78-year old man with a history of diabetes mellitus and suspected pancreas malignancy; who was brought because of fever disease with abdominal pain, and Vibrio cholerae bacteremia was documented, so antibacterial therapy was started, and his clinical condition resolved. Since this case was related to the ingestion of contaminated water, we notified the authorities so the infectious source may be controlled, and this intervention will prevent the occurrence of infections in persons in contact with this particular water source.